Parental reference photos do not always improve the accuracy of forensic age progressions. Issue 6 (November 2020) - Provenzano, Andrew C.; Lampinen, James M.; Erickson, William B.; Frowd, Charlie; Mahoney, Greg
Highlights: Age-progressions are less similar for age-progressions across wider age-range. Parental reference age-progressions across a wider age-range are less similar. Recognition memory worse for age-progressions across wider age-gap. Forensic artists may benefit from not relying on biological references. Abstract: During long-term missing children cases, forensic artists construct age-progressions to estimate the child's current appearance. It is commonly believed that incorporating information about the child's biological relatives is critical in accurately estimating the child's current appearance. However, some evidence suggests that predicting appearance based on inheritance of features may be error prone. The present studies examine whether age-progressions constructed with the aid of a biological reference photos led to better recognition than those constructed without a biological reference. We also investigated whether there would be any variation depending on the age-range of the age-progressions. Eight professional forensic artists created age-progressions based upon photographs provided by each of our eight targets. Half of their age progressions with the aid of parental reference photos and half without parental reference photos. Furthermore, half were age-progressed across a longer age-range (5–20 years) and half covered a shorter age-range (12–20 years). In Experiment 1 similarity scores were higher over shorter age-ranges. Further, across longer age-ranges age-progressions created with the aid of a parental reference were lower than those without a reference. In Experiment 2 recognition performance was higher across shorter age-ranges. Additionally, across longer age-ranges age-progressions created with the aid of a parental reference were recognized worse than those without a reference. These results suggest that in long-term missing person cases, forensic artists may benefit from not relying on biological references. Finally, consistent with previous research (e.g. Lampinen et al., 2012) age-progressions provided no benefit over using outdated photographs.